The Mystery of Russia’s Low Unemployment Rate - Vlasova, Ekaterina; Janíčko, Martin, 1983-; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This thesis focuses on the mystery surrounding the low unemployment rate in Russia and looks into the significance of factors like unemployment gap, output gap, labour productivity index and demographics which might influence the unemployment rate. The aim is to use standard econometric tools to process my own estimated data, and combine this with known publicly available quarterly time-series statistics to build a model to disclose the myth surrounding the relationship between the unemployment rate and the business cycle in Russia. Furthermore, it will look into additional factors, discussed in the theoretical part, which play a role in keeping the unemployment rate as low as it is.The findings of this thesis lead to the conclusion that macroeconomic indicators are less significant when it comes to interpreting the behaviour of the Russian unemployment rate. During this process I discover that the unemployment rate is misleading because it is hiding the real situation in the labour market. Therefore, the primary hypothesis that the Russian unemployment rate highly depends on demographic factors is further rejected.
Vedoucí práce: Martin Janíčko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses